Life at high salt concentrations, intracellular KCl concentrations, and acidic proteomes - Oren, Aharon (Frontiers in Microbiology, 2013)
Extremely halophilic microorganisms that accumulate KCl for osmotic balance (the Halobacteriaceae, Salinibacter) have a large excess of acidic amino acids in their proteins. This minireview explores the occurrence of acidic proteomes in halophiles of different physiology and phylogenetic affiliation. For fermentative bacteria of the order Halanaerobiales, known to accumulate KCl, an acidic proteome was predicted. However, this is not confirmed by genome analysis. The reported excess of acidic amino acids is due to a high content of Gln and Asn, which yield Glu and Asp upon acid hydrolysis. The closely related Halorhodospira halophila and Halorhodospira halochloris use different strategies to cope with high salt. The first has an acidic proteome and accumulates high KCl concentrations at high salt concentrations; the second does not accumulate KCl and lacks an acidic proteome. Acidic proteomes can be predicted from the genomes of some moderately halophilic aerobes that accumulate organic osmotic solutes (Halomonas elongata, Chromohalobacter salexigens) and some marine bacteria. Based on the information on cultured species it is possible to understand the pI profiles predicted from metagenomic data from hypersaline environments.